Anaerobic digestion of chicken manure: Mitigating process inhibition at high ammonia concentrations by selenium supplementation - ÇALLI, BARIŞ (PERGAMON-ELSEVIER SCIENCE LTD, 2018)
In this study, the anaerobic digestion of nitrogen-rich chicken manure from egg-laying hens was investigated via long-term continuous experiments with and without the addition of different trace elements. With trace element supplementation, a CH4 yield of 0.26 +/- 0.03 m(3) kg(-1) of volatile solids (VS) added was achieved at an organic loading rate (OLR) of 3.62 kg m(-3) day(-1) based on VS and total ammonia nitrogen (TAN) content greater than 7200 g m(-3). Selenium (Se) was identified as the critical trace element for the stable anaerobic digestion of chicken manure. The dominant methanogen in the reactors was the hydrogenotrophic methanogen Methanoculleus bourgensis. Therefore, we concluded that at elevated TAN concentrations, the CH4 production stimulated by Se supplementation likely occurred through syntrophic acetate oxidation. Without trace element supplementation, severe acetic and propionic acid accumulation occurred, causing the CH4 yield to decrease below 0.12 m(3) kg(-1) of VS added.
Keywords: Ammonia; Anaerobic digestion; Chicken manure; Syntrophic acetate oxidation; Trace elements; Selenium; SYNTROPHIC ACETATE OXIDATION; BIOGAS PRODUCTION; TRACE-ELEMENTS; POULTRY LITTER; WASTE; PERFORMANCE; METHANE; GROWTH; BIOAVAILABILITY; FERMENTATION